2022
DOI: 10.1038/s41419-021-04493-y
|View full text |Cite
|
Sign up to set email alerts
|

RNF12 is regulated by AKT phosphorylation and promotes TGF-β driven breast cancer metastasis

Abstract: Transforming growth factor-β (TGF-β) acts as a pro-metastatic factor in advanced breast cancer. RNF12, an E3 ubiquitin ligase, stimulates TGF-β signaling by binding to the inhibitory SMAD7 and inducing its proteasomal degradation. How RNF12 activity is regulated and its exact role in cancer is incompletely understood. Here we report that RNF12 was overexpressed in invasive breast cancers and its high expression correlated with poor prognosis. RNF12 promoted breast cancer cell migration, invasion, and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…29 RNF12, as a member of the ring finger protein family, has been reported to be dysregulated in many malignancies. 12,13,30 RNF12 was reported to be overexpressed in glioblastoma, which was correlated with a poor prognosis. 13 Furthermore, RNF12 was found to interact with and target RB1 for degradation to stimulate the MAPK pathway and promote the malignant proliferation of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 RNF12, as a member of the ring finger protein family, has been reported to be dysregulated in many malignancies. 12,13,30 RNF12 was reported to be overexpressed in glioblastoma, which was correlated with a poor prognosis. 13 Furthermore, RNF12 was found to interact with and target RB1 for degradation to stimulate the MAPK pathway and promote the malignant proliferation of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, RNF12 has been reported to be involved in the inactivation of X chromosome, embryonic development, cell differentiation and maintenance of neural function 11 . Recently, increasing research showed that RNF12 was involved in the development of cancer 12 . In glioblastoma, RNF12 was reported to be highly expressed and related to poor prognosis of patients 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, AKT promotes TGF‐β‐driven breast cancer metastasis by mediating RNF12 phosphorylation and enhancing RNF12 stability. 177 KNSTRN, a component of the mitotic spindle, phosphorylates AKT at Thr308 and Ser473 to activate AKT and promote bladder cancer metastasis. 178 TKT, a key metabolic enzyme in the pentose phosphate pathway (PPP), interacts with GRP78 to promote glycolysis by increasing AKT phosphorylation, which promotes CRC metastasis.…”
Section: Phosphorylationmentioning
confidence: 99%